Imidazolium functionalized carbon nanotubes for the synthesis of cyclic carbonates: reducing the gap between homogeneous and heterogeneous catalysis. Issue 24 (5th October 2016) - Buaki-Sogó, M.; Vivian, A.; Bivona, L. A.; García, H.; Gruttadauria, M.; Aprile, C.
Abstract : Single walled carbon nanotubes were functionalized with imidazolium based salts and successfully used as catalysts for the conversion of CO2 . The novel materials displayed excellent catalytic activity. Abstract : Single walled carbon nanotubes (SWCNTs) were functionalized with imidazolium salts bearing vinyl functionalities. An extremely high loading of active species was achieved through a straightforward one-pot procedure involving self-assembly of the imidazolium moieties followed by radical initiated polymerization of the double bonds. The materials were extensively characterized by transmission electron microscopy, Raman spectroscopy, nitrogen physisorption and combustion chemical analysis. The imidazolium functionalized SWCNTs displayed excellent catalytic activity for the reaction of CO2 and epoxides to produce cyclic carbonates as demonstrated by the excellent turnover numbers (TON). Moreover, they were used in multiple catalytic cycles without loss of activity.